Tinjauan Yuridis Dampak Perpanjangan Moratorium oleh World Trade Organization terhadap Pelaksanaan Perdagangan Digital Internasional Indonesia - Elverda Nadifa Rosyadi; Era Titis Cahya Rani; Fanny Putri Natasya; Edlin Andini Tiara Patiung (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Cross-border digital trade is increasingly happening and is in demand by Indonesian people. The implementation of the memotarium as a form of suspension of import duties on digital goods has had a significant impact on the implementation of international digital trade. The policy of extending the memotarium by the World Trade Organization (WTO) will certainly greatly influence the implementation of digital transactions in Indonesia and the legal policies that regulate this matter. This writing provides an understanding of the impact of the extension of the memotarium by the WTO on the implementation of digital transactions in Indonesia and Indonesia's regulatory arrangements in implementing the extension of the memotarium by the WTO. This problem will be studied through normative methods of literature study with an international trade law perspective through the study of legal regulations, journals, books and previous research. This writing will discuss Indonesian legal regulations as a form of implementation of the extension of the memotarium by the WTO as well as the impact felt by Indonesian digital transactions due to the extension of the memotarium by the WTO. The originality of the research explains the Indonesian regulations governing this matter and the influence of the memotarium extension on Indonesian digital transactions.